Phonon-engineered extreme thermal conductivity materials - Qian, Xin; Zhou, Jiawei; Chen, Gang (Nature materials, 2021)
Materials with ultrahigh or low thermal conductivity are desirable for many technological applications, such as thermal management of electronic and photonic devices, heat exchangers, energy converters and thermal insulation. Recent advances in simulation tools (first principles, the atomistic Green’s function and molecular dynamics) and experimental techniques (pump–probe techniques and microfabricated platforms) have led to new insights on phonon transport and scattering in materials and the discovery of new thermal materials, and are enabling the engineering of phonons towards desired thermal properties. We review recent discoveries of both inorganic and organic materials with ultrahigh and low thermal conductivity, highlighting heat-conduction physics, strategies used to change thermal conductivity, and future directions to achieve extreme thermal conductivities in solid-state materials. This Review provides an overview of experimental and theoretical methods for the understanding of thermal transport, summarizes recent progress in materials with ultrahigh (or low) thermal conductivities, and outlines strategies for the engineering of extreme thermal conductivity materials.